Hubungan Tingkat Stres Dan Indek Massa Tubuh Pada Mahasiswa Tingkat Akhir Fakultas Kedokteran Universitas Baiturrahmah - Zahara, Ayuni; Malik, Rifkind; Nani Jelmila, Sri; Rizki Saputra, Muhammad; Dhuha, Alief (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Academic stress is one of the challenges faced by students. Final year students, who are in the process of writing their theses, experience higher levels of stress compared to those who have not yet started. The stress encountered by these final year students can stem from both external and internal sources. Objective: To determine the relationship between stress levels and body fat composition among final year medical students at Universitas Baiturrahmah in the year 2019. Methods: The scope of this research encompasses Psychiatry and Nutrition Science. The study was conducted from March 2021 to March 2022. It is an observational analytic study. The accessible population for this study was all final year undergraduate medical students at Universitas Baiturrahmah from the 2019 cohort, totaling 99 samples, using a simple random sampling technique. Univariate data analysis was presented in frequency distribution, bivariate analysis used the Kolmogorov-Smirnov test, and data processing utilized the IBM SPSS software. Results: The most common stress level was normal, affecting 62 individuals (62.6%), and the most prevalent body fat composition was obesity, affecting 66 individuals (66.7%). There was no relationship found between stress levels and body fat composition among final year medical students at Universitas Baiturrahmah in 2019 (p=0.586). Conclusion: The predominant stress level among the students was normal, obesity was the most common body fat composition, and there was no correlation found between stress levels and body fat composition in final year medical students at Universitas Baiturrahmah for the year 2019.